An analysis of spatial correlates of terrorism using risk terrain modeling - Onat, Ismail (Terrorism and political violence, 2019)
The purpose of this study is to identify correlates of terrorism in space. It examines whether places with terrorist incidents show similar patterns with respect to the physical features across landscape, and tests the spatial influence of various features of environment on the incidence of terrorism. Drawing on the locations of violent terrorist offenses committed between 2008 and 2012, the study in Istanbul applies the Risk Terrain Modeling framework to terrorism. It uses data on police incidents and infrastructure (e.g., government buildings or parks). The analysis employs GIS techniques and an event count model, and combines all risky layers in a composite map to understand where the risk is higher. The study suggests a concentration of 1153 violent terrorist incidents relative to key physical factors by identifying seventeen potential risk factors, eight of which were significantly correlated in the model. Regardless of terrorists’ intent, the significantly associated establishments increase the risk in the surrounding areas where these features are located. The coexistence of leisure places such as bakeries, religious facilities, or eateries results in higher risks. While the environmental backcloth may constitute a risk for terrorism, its components may also help forecast the locations of terrorist incidents in the future.